Reconstituted High Density Lipoprotein (rHDL) Modulates Platelet Activity In Vitro and Ex Vivo - Lerch, Peter G.; Spycher, Martin O.; Doran, Jan E. (Thrombosis and Haemostasis, 1998)
A reconstituted high density lipoprotein (rHDL) prepared for clinical use was tested for its influence on platelet activity modulated by various stimuli. In a first series of in vitro experiments, rHDL was added to blood in a concentration series, and platelet rich plasma (PRP) was isolated. Platelets were stimulated with arachidonic acid, collagen, epinephrine or ADP, and platelet aggregation was assessed. rHDL mediated a dose dependent inhibition of the platelet activity. With purified platelets rHDL inhibited the release reaction induced by collagen, but not by thrombin, as measured by CD62P (P-Selectin) expression on the plasma membrane. Ex vivo experiments were performed with PRP from volunteers, previously infused with 25 mg rHDL/kg body weight and 40 mg rHDL/kg body weight, respectively. Platelet activity in PRP was assessed before, and up to 30 h after the end of the rHDL infusion. A transient inhibition of the platelet aggregation induced by arachidonic acid and collagen was observed which was more pronounced in the group receiving 40 mg rHDL/kg body weight. In both groups of experiments, in vitro and ex vivo, the inhibition of the platelet activity was also dependent on the stimulus used.